2011
DOI: 10.3945/jn.110.131433
|View full text |Cite
|
Sign up to set email alerts
|

Ovine Serum Immunoglobulin Has Immunomodulatory Effects in Growing Rats Gavaged with Salmonella enteritidis1

Abstract: In this study, we aimed to determine whether orally administered ovine serum Ig modulate aspects of immunity and associated gut microflora in growing rats challenged with Salmonella enteritidis. The 4 groups consisted of rats fed a casein-based control diet (BD; ungavaged) and 3 groups of rats gavaged with 1 × 10(7) viable Salmonella enteritidis and fed a BD diet, a BD diet containing freeze-dried ovine Ig (FDOI), or a BD diet containing inactivated ovine Ig (IOI). The rats were randomly allocated to 1 of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 28 publications
1
34
1
Order By: Relevance
“…Recently, we have reported that feeding a freeze-dried ovine serum Ig preparation selectively improves growth performance, the weight of some digestive organs and gut morphology in the growing rat (Balan et al, 2009). Dietary Ig preserved a higher degree of immunological activity and selectively altered the composition of the gut microbiota (upregulation of Lactobacillus species) in normal and in Salmonella enteritidis challenged growing rats (Balan et al, 2010(Balan et al, , 2011a(Balan et al, and 2011b. There are no reports in the literature, however, regarding the effects of ovine Ig on gut mucins in animals.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have reported that feeding a freeze-dried ovine serum Ig preparation selectively improves growth performance, the weight of some digestive organs and gut morphology in the growing rat (Balan et al, 2009). Dietary Ig preserved a higher degree of immunological activity and selectively altered the composition of the gut microbiota (upregulation of Lactobacillus species) in normal and in Salmonella enteritidis challenged growing rats (Balan et al, 2010(Balan et al, , 2011a(Balan et al, and 2011b. There are no reports in the literature, however, regarding the effects of ovine Ig on gut mucins in animals.…”
Section: Introductionmentioning
confidence: 99%
“…Increases were observed in the ileal and colonie digesta mainly because of an increase in the number of lactobacilli and a decrease in enterobacteria. Previous work with the same ovine Ig fraction also showed increases in the lactobacilli in the ileal and colonie digesta of Salmonella enteritidis-challenged rats (Balan, 2011;Balan et al, 2011b). The basis for this effect remains unknown.…”
Section: Discussionmentioning
confidence: 74%
“…Eleetrophoresis was performed at 130 V for 6 h in a IX TAE buffer at a constant temperature of 60°C. The DNA bands were visualized by ethidium bromide staining (50 |j.g/ mL) and then photographed (GelDoc XR 2000; Bio-Rad Laboratories; Balan, 2011 ;Balan et al, 2011b). Diversify Database (version 2003, Phoretix Software; Nonlinear Dynamics Ltd., Newcastle Upon Tyne, UK) was used to analyze the intensify, migration pattems, and total band numbers of the DGGE gel profiles within each lane of a gel and to determine Shannon's diversify index.…”
Section: Isolation Of Bacterial Dna From Digesta and Pcr-dggementioning
confidence: 99%
“…As a result, it is possible that an animal's immune system would be stronger and better adjusted to counter‐attack the full spectrum of microbial pathogens by producing antibodies against them. It is well documented that animal serum contains antibodies that are effective against a variety of microbial pathogens such as E. coli , Salmonella , Listeria , C. difficile , rotavirus and others (Balan, ; Balan, Han, Rutherfurd, et al, ; Balan, Han, Rutherfurd‐Markwick, et al, ; Balan et al, ; Han et al, ; Pierce et al, ). Therefore, serum Ig would provide passive antimicrobial protection (and from subclinical infection) by exclusion of opportunistic microbial pathogens.…”
Section: Resultsmentioning
confidence: 99%
“…Following which, a series of peer‐reviewed publications are found in the literature suggesting the various positive biological effects of ovine Ig preparation in different challenged and unchallenged animal models. When compared to casein‐based diet, ovine serum Ig supplemented diet was found to positively modulate growth, immunity, gut microbiota and gut mucins in both challenged (Balan, Han, Rutherfurd, Singh, & Moughan, ; Balan, Han, Rutherfurd‐Markwick, Singh, & Moughan, ; Balan & Moughan, ; Balan et al, ) and unchallenged (Balan, ; Balan, Han, Lawley, & Moughan, ; Balan et al, ; Balan, Han, Rutherfurd‐Markwick, Singh, & Moughan, ; Balan, Han, Singh, & Moughan, ) rodent models. Furthermore, recently a report was found showing that ovine Ig significantly reduces plaque formation and significantly modulates the oral and peripheral immunity in the cats (Balan et al, ).…”
Section: Introductionmentioning
confidence: 99%